ANALISIS SEBARAN TEMPERATUR DAN SALINITAS AIR LIMBAH PLTU-PLTGU BERDASARKAN SISTEM PEMETAAAN SPASIAL (STUDI KASUS : PLTU-PLTGU TAMBAK LOROK SEMARANG) - Haryono Setiyo Huboyo; Badrus Zaman (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Heat wastewater emitted by power plant near seashore will be dispersed to bulk seawater by stream.  The main  effects  generated  by  this  elevated  streams  is  deteriorating  of  benthic  and aquatic life productivity. Further impact is subjected to depleting dissolved oxygen and seawater salinity content. By means of spatial mapping, the pattern of temperature distribution would be revealed and its impact  could be predicted  by then. Measurements of 14 purposive sampling spots were conducted in the early morning, noon and afternoon within Tambak Lorok Port pond. Control  measurements  also  were  taken  in  the East  side  and  West  side  of  the  pond. Temperature distribution observed from the early morning through the afternoon exhibited the same pattern with dissolved oxygen distribution as well as stream pattern. Turbidity distribution accumulated  in  the  East  side,  mixed  with  domestic  waste  stream carrying  large  amount suspended  solids.  Salinity  distribution  showed  a  little  bit  different  pattern with  temperature distribution  considering  that  salinity  pattern  was  affected  by  incoming  streams from  bulk seawater in the Northwest and Northeast of the pond.